Pengaruh Kesadaran Wajib Pajak, Pengetahuan Perpajakan, Kualitas Pelayanan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak ( Studi Kasus Pada Wajib Pajak yang Terdaftar di KPP Pratama Klaten ) - Sari, Titra Ratna; , Drs. Muhammad Abdul Aris, M.Si (2015)
The purpose of this research was to test whether the tax payer awareness, know ledge of taxation, quality of service and tax penalties have a significant impact on taxpayer compliance. The population in this research is a registered tax payer in KPP Pratama Klaten. The sampling technique using incidental sampling. The samples were taken by using slovin. Primary research data are of the 100 respondents, a total of 83 questionnaires that can be processed obtained by distributing questionnaires to 100 respondents. Data analysis method used in this research is multiple linear regression analysis with the SPSS 21.0. The resulte of this research are knowledge of taxation, quality of service and tax penalties effect on tax compliance. While awareness of the tax payer has not effection tax compliance